Ritual, Sacredness, and Sustainability: A Thematic Exploration of Eco-Cultural Tourism in Tenganan Pegringsingan, Bali - Ghalih, Muhammad; Dewayani, Eka Kadharpa Utama (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2025)
This study investigates how ritual practices shape the development and governance of eco-cultural tourism in Tenganan Pegringsingan, an Indigenous Bali Aga village in eastern Bali. Grounded in an interpretivist framework and employing thematic analysis, the research draws on in-depth interviews with ritual elders, local artisans, tourism intermediaries, and community members. The findings reveal that rituals in Tenganan function not only as sacred expressions but also as boundary mechanisms, regulating tourist access and reinforcing collective identity. Tourism is not approached as a commercial imperative but as an opportunity for cultural affirmation, framed within customary law and spiritual ethics. The study identifies four key themes: ritual as a gatekeeping device, tourism as a platform for cultural narration, the moral economy of sacred space, and intergenerational shifts in cultural adaptation. Together, these themes illustrate how cultural sustainability in Tenganan is enacted through ritual logic, ethical hospitality, and controlled visibility. The paper contributes to scholarship on Indigenous tourism by highlighting how community agency, moral frameworks, and ancestral knowledge inform locally governed models of sustainable tourism. It offers theoretical and practical insights for decolonizing tourism narratives and reinforcing the role of intangible heritage in guiding tourism development.